2009
DOI: 10.1007/978-3-540-89208-3_437
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer based measurement of body movement for communication, play, and creative expression

Abstract: Abstract-This paper presents a newly designed wireless accelerometer-based movement measurement device. The device is capable of measuring activity ranging from gross body movements to more subtle vibrations emanating from the body, including laryngeal vibration and the mechanomyogram (mechanical vibrations from working muscles). The main body of the device, which is less than 20cm 3 in volume and weighs less than 50g, contains a microcontroller, wireless transceiver, battery, and one accelerometer. A suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A previous related study showed that laryngeal vibrations measured using an accelerometer could be harnessed as a channel of communication, facilitating play and creative expression [8]. That study applied this concept to assist children with physical disabilities to engage with toys and music-making activities to which they would otherwise have limited access.…”
Section: B Control Using Laryngeal Vibrationsmentioning
confidence: 99%
“…A previous related study showed that laryngeal vibrations measured using an accelerometer could be harnessed as a channel of communication, facilitating play and creative expression [8]. That study applied this concept to assist children with physical disabilities to engage with toys and music-making activities to which they would otherwise have limited access.…”
Section: B Control Using Laryngeal Vibrationsmentioning
confidence: 99%